197k views
1 vote
If A = 1 2 1 1 and B= 0 -1 1 2 then show that (AB)^-1 = B^-1 A^-1

help meeeee plessss ​

User Ricardo C
by
5.3k points

1 Answer

3 votes


A = \begin{bmatrix}1&2\\1&1\end{bmatrix} \implies A^(-1) = \frac1{\det(A)}\begin{bmatrix}1&-1\\-2&1\end{bmatrix} = \begin{bmatrix}-1&1\\2&-1\end{bmatrix}

where det(A) = 1×1 - 2×1 = -1.


B = \begin{bmatrix}0&-1\\1&2\end{bmatrix} \implies B^(-1) = \frac1{\det(B)}\begin{bmatrix}2&1\\-1&0\end{bmatrix} = \begin{bmatrix}2&1\\-1&0\end{bmatrix}

where det(B) = 0×2 - (-1)×1 = 1. Then


B^(-1)A^(-1) = \begin{bmatrix}2&1\\-1&0\end{bmatrix} \begin{bmatrix}-1&1\\2&-1\end{bmatrix} = \begin{bmatrix}-1&3\\1&-2\end{bmatrix}

On the other side, we have


AB = \begin{bmatrix}1&2\\1&1\end{bmatrix} \begin{bmatrix}0&-1\\1&2\end{bmatrix} = \begin{bmatrix}2&3\\1&1\end{bmatrix}

and det(AB) = det(A) det(B) = (-1)×1 = -1. So


(AB)^(-1) = \frac1{\det(AB)}\begin{bmatrix}1&-3\\-1&2\end{bmatrix} = \begin{bmatrix}-1&3\\1&-2\end{bmatrix}

and both matrices are clearly the same.

More generally, we have by definition of inverse,


(AB)(AB)^(-1) = I

where
I is the identity matrix. Multiply on the left by A ⁻¹ to get


A^(-1)(AB)(AB)^(-1) = A^(-1)I = A^(-1)

Multiplication of matrices is associative, so we can regroup terms as


(A^(-1)A)B(AB)^(-1) = A^(-1) \\\\ B(AB)^(-1) = A^(-1)

Now multiply again on the left by B ⁻¹ and do the same thing:


B^(-1)\left(B(AB)^(-1)\right) = (B^(-1)B)(AB)^(-1) = B^(-1)A^(-1) \\\\ (AB)^(-1) = B^(-1)A^(-1)

User Pmarflee
by
5.1k points